Relationships are Constructed from Generalized Unconscious Social Images Kept in Steady Locations in Mental Space - Walter O. Ötsch; Wolfgang Walker; Lucas A. C. Derks (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2014)
The social panorama approach is a psychotherapeutic method based on the view that generalized unconscious spatial imagery forms the cognitive foundation of social life. It appears to be an efficient therapeutic tool for solving a wide range of relational issues and may inspire research on space in social cognition. The leading principle of the social panorama model is "relation equals location", which means that people keep the generalized images of relevant others in steady locations in the mental space around them. The exact location of such an image governs the emotional quality of the relationship. We tested the prediction that moving a social image will change the emotional meaning of the relationship involved (i.e., relation equals location). To this end, we measured how increasing the distance to the image of a beloved alters the emotional experience. Our results show that, when asked to triple the distance to the image of a loved one, the participants exhibited a significant decrease in the intensity and dramatic shifts in the quality of their emotions.
Keywords: 330; social panorama; psychotherapeutic method